2021
DOI: 10.1039/d0fo03220d
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of fucoidan against ethanol-induced liver injury through maintaining mitochondrial function and mitophagy balance in rats

Abstract: For alcoholic liver disease (ALD), mitophagy was reported as a promising therapeutic strategy to alleviate the hepatic lesion elicited by ethanol. This study was to investigate the regulatory effects of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…As discovered by Zhao et al, in the livers of alcohol-fed rats, decreased antioxidant enzymes, such as GSH and CAT, increased lipid peroxidation products, and lipid metabolic disorders were observed. Fucoidan pretreatment restored the normal levels of antioxidant enzymes, alleviated oxidative damage, and improved the lipid metabolic disorders [ 41 ], indicating that fucoidan prevented the occurrence of FALD to a certain extent. Ma et al, reported the therapeutic effect of resveratrol on rat FALD and found that ROS levels in the livers of FALD rats were controlled after the administration of resveratrol, which in turn improved FALD [ 42 ].…”
Section: Mitochondrial Dysfunction and Chronic Liver Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…As discovered by Zhao et al, in the livers of alcohol-fed rats, decreased antioxidant enzymes, such as GSH and CAT, increased lipid peroxidation products, and lipid metabolic disorders were observed. Fucoidan pretreatment restored the normal levels of antioxidant enzymes, alleviated oxidative damage, and improved the lipid metabolic disorders [ 41 ], indicating that fucoidan prevented the occurrence of FALD to a certain extent. Ma et al, reported the therapeutic effect of resveratrol on rat FALD and found that ROS levels in the livers of FALD rats were controlled after the administration of resveratrol, which in turn improved FALD [ 42 ].…”
Section: Mitochondrial Dysfunction and Chronic Liver Diseasementioning
confidence: 99%
“…Morphological structure Mitochondria are swollen, the inner membrane is destroyed, the cristae have disappeared, and the membrane potential is decreased. [41,43,45,46] Energy metabolism Fatty acids have accumulated and ATP synthesis is decreased. [39][40][41][42][43]46] ROS GSH and SOD are decreased, and ROS is increased.…”
Section: Types Of Dysfunction Specific Characterization Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of FFA in cells render the mitochondria prone to overproduction of reactive oxygen species (ROS; Zorov et al, 2014), which can lead to mitochondrial damage (Sanz et al, 2006) and aggravate hepatic lipidosis (Rector et al, 2010). Thus, timely elimination of damaged mitochondria contributes to reduction in ROS production and helps maintain lipid metabolism homeostasis (Rector et al, 2010;Zhao et al, 2021;Cioffi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%